THE EFFECT OF INVESTMENT DECISIONS, FIRM SIZE, AND DIVIDEND POLICY ON FIRM VALUE (Study on Infrastructure Sector Companies on the IDX) - Safira Hayu Pramesti Kirana; Sayu Ketut Sutrisna Dewi (Adisam Publisher, 2025)
Firm value refers to the present value of future earnings and acts as an important indicator for the market in evaluating a company’s overall performance. This study aims to examine the effect of investment decisions, firm size, and dividend policy on the firm value of infrastructure companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The population consists of 57 infrastructure companies, with 15 selected using purposive sampling. The data were analyzed using multiple linear regression. The results show that investment decisions and firm size have a significant positive effect on firm value, while dividend policy has a positive but not significant effect. These findings provide evidence of how financial decisions influence firm value. For company managers, this study offers input to improve firm value, and for investors, it can be used as a reference in making investment decisions.